Charis and charisma : David Yonggi Cho and the growth of Yoido Full Gospel Church. - Young-Gi, Hong (Regnum studies in mission., 2003)
Founded by David Yonggi Cho, Yoido Full Gospel Church is the world's largest church. This book discusses the factors responsible for its phenomenal growth and expounds on the roles of leadership, the Holy Spirit, prayer, preaching, cell groups, and creativity in promoting church growth. It focusses on God's grace (charis) and inspiring leadership (charisma) as the two essential factors for church growth, and in this context examines the part David Yonggi Cho's personal charisma and his ideas and principles have played in causing growth. The purpose of the book is to present a model for church growth worldwide.